Editorial - Chaleplioglou, Artemis (Journal of Integrated Information Management, 2025)
Dear Colleagues, JIIM is an international, multidisciplinary, blind, peer-reviewed, open-access electronic journal that publishes research on all aspects of Information Science and Integrated Information Management. JIIM is the official journal of the Department of Archival, Library & Information Studies, University of West Attica (UNIWA), and it is available through the Greek National Documentation Centre (EKT) ePublishing platform for electronic journals: https://ejournals.epublishing.ekt.gr/index.php/jiim. The current issue publishes research articles on the artificial ageing of paper, decorated papers in bookbinding, the alignment of scholarly journal submission evaluation criteria in Library and Information Science, Communication, History and Philosophy, and problem-based e-learning. Initially, the scientific foundations, methodologies, and technologies employed in the artificial aging of paper reflect the effects of various environmental conditions on books, journal volumes, and other physical paper materials in libraries. Experimental evaluation of artificial aging can inform the development of mathematical models of paper degradation, which is valuable for storage decisions in libraries. The following paper also addresses the physical condition of books and focuses on 19th-century bookbinding. It proposes a systematic metadata schema to support library management. The decorated papers used in books as covers, cover parts, or endpapers reflect physical characteristics associated with the historical bookbinding techniques applied or with the paper's origin. The third paper outlines the evaluation criteria for scholarly journal submissions in Library and Information Science, Communication, History, and Philosophy. Eleven criteria were found: adequacy of data to support the conclusions, consistency of conclusions with research goals and data, clarity and readability of the evaluated article, balance and accuracy of bibliographic references, compliance with ethical standards of research, reliability and reproducibility of methodology, significance of the quality and clarity of tables, graphs and figures, relevance and originality of the research question or topic, optimization of the title, abstract keywords for search engines, effectiveness of the introduction in establishing research framework, originality, and aims, and coherence and logic of the article’s argument. Finally, the problem-based e-learning (PBL) application at the Department of Business Administration at the University of West Attica during and after the Covid-19 pandemic, when distance education was widely implemented, used Microsoft Teams analytics and the Motivated Strategies for Learning Questionnaire (MSLQ). The findings indicated that the proposed instructional design approach, based on the PBL method, had a positive effect on students' intrinsic motivation and self-efficacy, but no effect on their extrinsic motivation. We welcome proposals for Special Issues, which should be emailed to Associate Professor Dimitrios Kouis (dkouis@uniwa.gr) or Assistant Professor Artemis Chaleplioglou (artemischal@uniwa.gr). We expect your contributions, active support, comments, and suggestions for improvement. The JIIM Editorial Team wishes all of you Happy Holidays and a Happy New Year. Assistant Professor - Editor Artemis Chaleplioglou Department of Archival, Library and Information Studies University of West Attica